Feminist perspectives on sustainable development - Harcourt, Wendy 1959- (Zed Books Ltd, in association with Society for International Development, Rome, 1994)
This collection captures the vitality and urgency of feminists' responses to the environment and development debate. The authors - researchers, activists and policy-makers from North and South - offer new ways of challenging the present dominating knowledge-systems and development institutions, and discuss the difficulties women face on the margins of the development process. Contributions on resource management, power, knowledge production, culture, development institutions and politics, health and economics, show how gender relations are not simply a footnote to our understanding of history and societies, but must be central to the development discourse. In so doing, they suggest that diversity itself is necessary to the creation of new paradigms of development that are built upon gender equity, secure livelihoods, ecological sustainability and political participation.